PROFITABILITY INTERVENING DETERMINANT TRANSFER PRICING IN TECHNOLOGY SECTOR COMPANIES INDONESIA - Eka Puji Sri Rahayu; Alia Sukma Setiawati; Selly Buana Ramadiani; Hakim, Mohamad Zulman; Hustna Dara Sarra; Sri Yanto (ZILLZELL MEDIA PRIMA, 2025)
This study evaluates the influence of tax burden, leverage, and company size on transfer pricing decisions with profitability as an intervening variable, using data from technology companies listed on the Indonesia Stock Exchange for the 2021-2023 period. Data analysis was carried out using the panel data regression method and using the Random Effect Model (REM) model. The results showed that the tax burden and company size had a significant positive effect on transfer pricing decisions, while leverage did not show a significant effect. Profitability was shown to mediate the relationship of leverage and company size to transfer pricing, but did not mediate the effect of tax burden. These findings underscore that large and profitable companies tend to utilize transfer pricing as a strategy to reduce their tax burden.